2022
DOI: 10.3389/fmicb.2021.794441
|View full text |Cite
|
Sign up to set email alerts
|

Human Milk Oligosaccharides Exhibit Biofilm Eradication Activity Against Matured Biofilms Formed by Different Pathogen Species

Abstract: Human milk oligosaccharides (HMOs) have been shown to exhibit plenty of benefits for infants, such as prebiotic activity shaping the gut microbiota and immunomodulatory and anti-inflammatory activity. For some pathogenic bacteria, antimicrobial activity has been proved, but most studies focus on group B streptococci. In the present study, we investigated the antimicrobial and antibiofilm activities of the total and fractionated HMOs from pooled human milk against four common human pathogenic Gram-negative spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…HMOs can inhibit the adhesion of pathogens by acting as decoy receptors that bind harmful bacteria, including Pseudomonas aeruginosa, Salmonella enterica, and enteropathogenic Escherichia coli [43]. One study found that HMOs isolated from milk samples of nine healthy participants could suppress the growth of Staphylococcus aureus, Enterococcus faecium, and Enterococcus faecalis, regardless of whether the bacteria were planktonic or in biofilms [44]. HMOs also have the ability to enhance cytokine secretion in vitro [45].…”
Section: Human Milk Oligosaccharidesmentioning
confidence: 99%
“…HMOs can inhibit the adhesion of pathogens by acting as decoy receptors that bind harmful bacteria, including Pseudomonas aeruginosa, Salmonella enterica, and enteropathogenic Escherichia coli [43]. One study found that HMOs isolated from milk samples of nine healthy participants could suppress the growth of Staphylococcus aureus, Enterococcus faecium, and Enterococcus faecalis, regardless of whether the bacteria were planktonic or in biofilms [44]. HMOs also have the ability to enhance cytokine secretion in vitro [45].…”
Section: Human Milk Oligosaccharidesmentioning
confidence: 99%
“…Recent research has suggested that prebiotic HMOs may improve the ability of beneficial microbiota to adhere to an infant's gastrointestinal wall by modulating the expression of bacterial adhesins [57][58][59]. Microbial contact, known as adhesion, occurs between the surface components of bacterial cells entering an infant's gut, such as lactobacilli, and the surfaces of the host's digestive tract.…”
Section: Enhancing Microbial Adhesionmentioning
confidence: 99%
“…HMO inhibits the activity of norovirus, rotavirus, and influenza virus by balancing cytokine response, stimulating the maturation of epithelial cells, and reducing viral adherence to target cells ( 47 ). It can also inhibit many Gram-negative pathogenic bacteria such as Klebsiella pneumoniae , Acinetobacter baumannii , Pseudomonas aeruginosa , and Burkholderia cenocepacia , and many Gram-positive bacteria such as Staphylococcus aureus , Enterococcus faecium , and Enterococcus faecalis ( 52 ). Moreover, it has been demonstrated that Osteopontin can inhibit rotavirus infection in vivo , and glycerol monolaurate has been described to have a wide range of microbial inhibitory properties ( 47 ).…”
Section: Lack Of Breastmilk Causes Illness and Even Death In Newbornsmentioning
confidence: 99%